Environmental Accountability through Business Ethics, Responsibility, Morals and Legal Obligations - Darmawan, Didit (Metromedia, 2022)
Government regulations and business sector implementation regarding environmental accountability remain suboptimal. This study aims to analyze the role of moral reasoning in enhancing environmental accountability. The research adopts a normative juridical approach, focusing on an in-depth examination of the general principles of environmental accountability as stipulated in existing laws and regulations. Through this study, it is emphasized that every business actor is obliged to uphold environmental accountability not only as a legal mandate but also as an ethical imperative within business practices. Social and environmental responsibility reflects a company’s commitment and obligation to account for the impacts of its operations across social, economic, and environmental dimensions. These impacts must be managed in a way that avoids harm and instead contributes positively to societal welfare and environmental sustainability.